2009
DOI: 10.1080/14649370902823371
|View full text |Cite
|
Sign up to set email alerts
|

College rank and neo‐liberal subjectivity in South Korea: the burden of self‐development

Abstract: This paper explores the ways in which contemporary college students in South Korea inhabit new discourses of human development in the context of South Korea's neo-liberal turn and globalization. By using ethnographic methods, we examine the lives of college students across three campuses, a top-tier private school and two mid-tier schools. The college students who we introduce all aspire to and accept the burden of managing their personal formation for a changing world. We note that the individuated way in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 20 publications
(17 reference statements)
2
55
0
Order By: Relevance
“…Considering national populations (India,1.17 billion;China,1.3 billion;and Korea,49 million), the ratio of Korean students in the US higher education is 19 times that of India, and 25 times that of China. Koreans' enthusiasm for learning English and for workplace opportunities favoring those with US degrees have been well documented (Abelmann, Park, and Kim 2009;Park and Abelmann 2004;Song et al 2007;. It is therefore surprising that Korean students' extraordinary obsession with US higher education has rarely been studied in Korea or elsewhere.…”
Section: Introductionmentioning
confidence: 92%
“…Considering national populations (India,1.17 billion;China,1.3 billion;and Korea,49 million), the ratio of Korean students in the US higher education is 19 times that of India, and 25 times that of China. Koreans' enthusiasm for learning English and for workplace opportunities favoring those with US degrees have been well documented (Abelmann, Park, and Kim 2009;Park and Abelmann 2004;Song et al 2007;. It is therefore surprising that Korean students' extraordinary obsession with US higher education has rarely been studied in Korea or elsewhere.…”
Section: Introductionmentioning
confidence: 92%
“…The described doxic belief was consistent with studies in neighbouring South Korea by Park (2010) analysing the mass-media's disregard of the privileged backgrounds of successful English learners, instead focusing on the individual's sense of responsibility and diligence that deserved the assignment of a morally superior position, while other ethnographic research showed that English speakers' in fact construed their own proficiency as the result of higher moral worth and character (Abelmann, Park, & Kim, 2009;Song, 2009). This sociallyconstrued moral worth based around English proficiency, was elaborated by Fonnie:…”
Section: Adamsupporting
confidence: 63%
“…In a similar vein, Nancy Abelmann et al (2009) identify a strong discourse of selfdevelopment prevalent in the narratives of college students in South Korea. Due to the limited number of jobs offered in the formal sector, only a small fraction of these young people will ever be able to secure formal paid employment.…”
Section: 4mentioning
confidence: 91%